Combination of Anti-PD-1 Antibody, Anlotinib and Pegaspargase “Sandwich” With Radiotherapy in Localized Natural Killer/T Cell Lymphoma - Sun, Peng; Wang, Yu; Yang, Hang; Chen, Cui; Nie, Man; Sun, Xiao-Qing; He, Xiao-Hua; Huang, Kang-Ming; Huang, Jia-Jia; Li, Zhi-Ming (Frontiers in Immunology, 2022)
Asparaginase/pegaspargase containing regimens combined with radiotherapy are highly effective and considered the cornerstone of localized Natural killer/T-cell lymphoma (NKTL) treatment. However, these chemotherapy regimens inevitably cause relatively high incidence of treatment-related adverse events (TRAEs). Herein we retrospectively evaluated the efficacy and safety of the combined regimen of anti-PD-1 antibody, anlotinib and pegaspargase “sandwich” with radiotherapy in localized NKTL. Anti-PD-1 antibody and pegaspargase at 2500 U/m2 were administered on day 1, while anlotinib (12 mg once a day) was orally administered on days 1-14. The treatment was repeated every 3 weeks. All the eight patients included received 3 cycles of the regimen followed by radiotherapy and an additional 3 cycles. The overall response rate was 100%, and the complete response rate was 87.5%. With a median follow-up time of 35.5 months (range, 34.03-40.90 months), median PFS and OS times were not reached. The 3-year PFS and OS rates were 100% and 100%, respectively. All patients were alive at the last follow-up. No treatment-related death and no grade 4 TRAE was reported. No grade 3/4 hematological toxicity was detected, and half of the patients didn’t report any hematological toxicity. This study indicates that anti-PD-1 antibody combined with anlotinib and pegaspargase is a promising chemoradiotherapy regimen for localized NTKL, with mild toxicity and good tolerance.